Analyzing the antagonistic potential of the lichen microbiome against pathogens by bridging metagenomic with culture studies - Cernava, Tomislav; Müller, Henry; Aschenbrenner, Ines A.; Grube, Martin; Berg, Gabriele (Frontiers in Microbiology, 2015)
Naturally occurring antagonists towards pathogens play an important role to avoid pathogen outbreaks in ecosystems, and they can be applied as biocontrol agents for crops. Lichens present long-living symbiotic systems continuously exposed to pathogens. To analyze the antagonistic potential in lichens, we studied the bacterial community active against model bacteria and fungi by an integrative approach combining isolate screening, omics techniques and high resolution mass spectrometry. The highly diverse microbiome of the lung lichen (Lobaria pulmonaria (L.) Hoffm.) included an abundant antagonistic community dominated by Stenotrophomonas, Pseudomonas and Burkholderia. While antagonists represent 24.5% of the isolates, they were identified with only 7% in the metagenome; which means that they were overrepresented in the culturable fraction. Isolates of the dominant antagonistic genus Stenotrophomonas produced spermidine as main bioactive component. Moreover, spermidine-related genes, especially for the transport, were identified in the metagenome. The majority of hits identified belonged to Alphaproteobacteria, while Stenotrophomonas-specific spermidine synthases were not present in the dataset. Evidence for plant growth promoting effects was found for lichen-associated strains of Stenotrophomonas. Linking of metagenomic and culture data was possible but showed partly contradictory results, which required a comparative assessment. However, we have shown that lichens are important reservoirs for antagonistic bacteria, which open broad possibilities for biotechnological applications.